2003
DOI: 10.1002/pssc.200303360
|View full text |Cite
|
Sign up to set email alerts
|

Hydride vapor phase epitaxy of AlN: thermodynamic analysis of aluminum source and its application to growth

Abstract: A thermodynamic analysis of the generation of gaseous aluminum chlorides by the reaction between aluminum (Al) metal and hydrogen chloride (HCl) gas is described for hydride vapor phase epitaxy (HVPE) of AlN. Regardless of the hydrogen mole fraction in the carrier gas, the major species of aluminum chloride is AlCl when the temperature of the Al metal is above 790 °C and is AlCl 3 when the temperature is below 790 °C. Since AlCl 3 is less reactive with quartz (SiO 2 ) than AlCl, HVPE of AlN is possible using A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
90
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 7 publications
3
90
0
1
Order By: Relevance
“…However, AlN growth was difficult due to the violent reaction between AlCl of the source gas and the quartz reactor. Fortunately, when the temperature of the source zone is below 700 o C, AlCl 3 is predominantly produced, which was less reactive with quartz [3]. This confirmed the possibility of AlN growth by HVPE.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…However, AlN growth was difficult due to the violent reaction between AlCl of the source gas and the quartz reactor. Fortunately, when the temperature of the source zone is below 700 o C, AlCl 3 is predominantly produced, which was less reactive with quartz [3]. This confirmed the possibility of AlN growth by HVPE.…”
supporting
confidence: 60%
“…This confirmed the possibility of AlN growth by HVPE. The earlier reports include HVPE growth of AlN on sapphire or SiC substrate [3][4][5]. We have recently reported fabrication of thick AlN film by the low-pressure HVPE (LP-HVPE) on AlN/sapphire template, and succeeded in fabrication of AlN film that has mirror-like surface at the growth temperature above 1150 o C with growth rate up to 20 µm/h, and atomic steps at 1200 o C with growth rate of 2.1 µm/h by LP-HVPE [6,7].…”
mentioning
confidence: 98%
“…In the past, HVPE of AlN has seldom been studied because the molten Al or hot AlCl gas generated at the source zone reacts violently with the quartz (SiO 2 ) reactor [7]. However, the present authors recently reported that HVPE of AlN using AlCl 3 , which does not react with quartz, is possible by preferential generation of AlCl 3 at the source zone [7,8]. Exploiting this fact, other research groups have also investigated HVPE of AlN [9,10].…”
Section: Introductionmentioning
confidence: 85%
“…As is widely known, 2-inch-diameter GaN wafers have been massproduced by separating thick HVPE GaN layers from sapphire [5] or GaAs [6] starting substrates. In the past, HVPE of AlN has seldom been studied because the molten Al or hot AlCl gas generated at the source zone reacts violently with the quartz (SiO 2 ) reactor [7]. However, the present authors recently reported that HVPE of AlN using AlCl 3 , which does not react with quartz, is possible by preferential generation of AlCl 3 at the source zone [7,8].…”
Section: Introductionmentioning
confidence: 89%
“…Source gases were AlCl 3 generated by a reaction of Al metal and HCl gas, and NH 3 [5]. Carrier gas was a mixture of 70% H 2 and 30% N 2 .…”
mentioning
confidence: 99%